Global Governance of Seeds: Complementarities and Conflicts between Environment, Intellectual Property and Free Trade - Perelmuter, Tamara (2020)
This article analyzes the dynamics of global seed governance. It is an inherently conflictive process that concerns the regulations on access, use and control of seeds, derived from power disputes between a multiplicity of actors with diverse and conflicting interests. The study is focused on the current contradictory tendencies of appropriation and conservation of seeds, based on the analysis of two blocks of pacts with divergent positions that affect their governance. On the one hand, those pacts aimed at the appropriation of seeds through intellectual property. On the other hand, those inspired by an environmental rationality aimed at its conservation. The interrelationships between both blocks seek to complement each other, generating a certain synergy despite having different objectives. However, the link between the two is not symmetrical and intellectual property treaties have limited the scope of the environmental agenda.